Fluidization of a horizontally driven granular monolayer - Heckel, Michael; Sack, Achim; Kollmer, Jonathan; Pöschel, Thorsten (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2015)
We consider the transition of a horizontally vibrated monodisperse granular monolayer between its condensed state and its three-dimensional gaseous state as a function of the vibration parameters, amplitude, and frequency as well as particle number density. The transition is characterized by an abrupt change of the dynamical state which leaves its fingerprints in several measurable quantities including dissipation rate, sound emission, and a gap size which characterizes the sloshing motion of the material. The transition and its pronounced hysteresis is explained through the energy due to the collective motion of the particles relative to the container.